Case report: Fetal cervical immature teratoma and copy number variations - Li, Dianjie; Gao, Hong; Zheng, Wanting; Jin, Chunzhu; Huang, Yuxin; Pan, Shilei (Frontiers in Oncology, 2022)
Fetal cervical teratoma is a rare congenital neck tumor. Here, we report a case of a fetus with an anterior solid neck tumor that was confirmed to have an immature teratoma by histology. A duplication was found at chromosome 14q24.1-q24.3 of the fetus in chromosome microarray (CMA) and whole exome sequencing (WES), which was a copy number variation (CNV) and a probably new-onset. Ultrasound coupled with magnetic resonance imaging (MRI) can be considered to be a relatively reliable diagnostic tool, whereas ex-utero intrapartum therapy or resection of the tumor mass on placental support may improve the chances of the newborn’s survival. Strangely, the same duplication occurred on her next fetus that was found with complex congenital heart malformations. CNV at chromosome 14q24.1-q24.3 needs to be paid more attention.